DETEKSI ANTI GLUTAMIC ACID DECARBOXILASE/TYROSINE PHOSPHATASE (ANTI GAD/IA2) PADA PENDERITA DM TIPE 1 ANAK - Puspa Wardhani; S Darmadi; M Faizi; Netty Harjantien (Indonesian Association of Clinical Pathologist and Medical laboratory, 2008)
Our study evaluated anti GAD/IA2 levels in Type 1 DM patients in Dr. Soetomo Hospital Surabaya. We conducted cross sectionalstudy, involving Type 1 DM patients that already been established (C-Peptide bellow normal). Patient’s age range was from 2.8 yearsold to 17 years old, so they were regarded as children. We used anti GAD/IA2 reagents from Euroimmun wich had basic principal EIA.Twelve patients was involved in this study. The average level of anti GAD/IA2 was 210.37 IU/mL. The Average level of anti GAD/IA2was higher in female than male patients (227.38 IU/mL dan 162 IU/mL). All patients had anti GAD/IA2. This examination can beusefull for screenimg one who has high risk in developing type 1A DM, especially first degree relatives.